2019
DOI: 10.6007/ijarbss/v9-i2/5553
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy and the Performance of the Manufacturing Sector in Nigeria (1986-2017)

Abstract: This study examined the effect of monetary policy on the performance of the Manufacturing sector in Nigeria. The explanatory variables are monetary policy rate, Treasury bills rate, Cash reserve requirement and money supply; while the dependent variable is the Manufacturing (MANU) sector output. The study adopted an ex-post facto research design and used secondary data obtained from the CBN Statistical Bulletin. The study covered a period of 32 years (1986 to 2017). The data were subjected to Augmented Dicker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 4 publications
0
6
1
Order By: Relevance
“…Hence, the lending difficulties will reduce the rate of investment, output and financial performance. Nevertheless, the result is contrary to the works of Osmond, Egbulonu and Emerenini (2015), Uju and Oguchukwu (2021) and Osakwe et al, (2019) who found a significant positive relationship between monetary policy and manufacturing sector performance.…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…Hence, the lending difficulties will reduce the rate of investment, output and financial performance. Nevertheless, the result is contrary to the works of Osmond, Egbulonu and Emerenini (2015), Uju and Oguchukwu (2021) and Osakwe et al, (2019) who found a significant positive relationship between monetary policy and manufacturing sector performance.…”
Section: Resultscontrasting
confidence: 95%
“…The Nigerian government has made intensive efforts at diversifying the economy. The efforts were directed at policies that could enhance the growth of the different sectors of the Nigerian economy including the manufacturing sector (Osakwe, Ibenta & Ezeabasili, 2019). Moreover, understanding the accurate channels of monetary policy to the manufacturing sector can help in achieving sustainable growth and development of any nation's economy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that a unit increase in vegetable oil production, commercial loan extended to manufacturing industry, 1 st lag of broad money supply and 1 st lag of prime lending rate made significant positive impact on vegetable oil production at the past. However, Osakwe et al, (2019) reported that unit rise in money supply leads to about 9% increase in the output from the manufacturing sector of Nigeria economy. The coefficients that had negative significant impact on vegetable oil production in Nigeria at the past were current inflation rate, 1 st lag of inflation rate and current broad money supply.…”
Section: Variablesmentioning
confidence: 99%
“…Many sub-Saharan African nations like Nigeria have experienced a variety of economic difficulties, including sluggish development and economic instability, despite its abundance of natural and mineral resources (Osakwe, Ibenta, & Ezeabasili, 2019). As a result, unemployment, inflation, non-productivity, and a balance-of-payments deficit remained the norm.…”
Section: Introductionmentioning
confidence: 99%